Attenuated Salmonella Carrying IL-21-siRNA-CCR2 Co-expression Plasmid Enhances Anti-tumor Immune Response in Lung Cancer-bearing Mice - Li, Jing; Li, Kun; Yang, Jinhua; Mo, Mingyu; Han, Bingran; Chen, Jinwei; Geng, Jiaxin; Lei, Mengyu; Chen, Pengfei; Shao, Mingguang; Jiang, Hanyu; Zhao, Tiesuo; et al. (Current Gene Therapy, 2025)
<span class=
Keywords: IL-21